Insight into the natural history of primary biliary cirrhosis: A systemic review of data from placebo-controlled clinical trials - Xu, Ping; Li, Lan; Li, Guogang; Yu, Chaohui; Li, Youming (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: The natural history of primary biliary cirrhosis (PBC) is extremely variable. The extraction and analysis of available information from placebo-treated patients in randomized controlled trials of PBC treatment would facilitate the study of the natural history of PBC. The aim of the present study was to determine important clinical information regarding the natural history of PBC patients without effective treatment. Materials and Methods: A search of the PubMed, EMBASE and Cochrane Library databases was performed by two authors. Twelve randomized placebo-controlled clinical trials for PBC patients without decompensated cirrhosis were retrieved for further review. Pooled estimates of biochemical measurements, histological scores and clinical outcomes associated with PBC were calculated in the placebo group. Results: Placebo-treated PBC patients displayed a significant decrease in serum alkaline phosphatase and very slight fluctuations in the other biochemical parameters during the 2-year follow-up. Meanwhile, histological progression was observed in 39.4% of the placebo-treated patients, and a moderate deterioration in histological scores was noted after 2 years. The pooled 2-year rates of death, transplantation and development of varices were 11.4%, 8.7% and 10.6%, respectively, in placebo-treated PBC patients. Conclusion: This review provides a foundation for further epidemiologic investigations in untreated patients and ursodeoxycholic acid-resistant patients with PBC. Biochemical responses after 2 years may provide some information on disease progression and therapeutic response in PBC.